The content of the work carried out on the correct pronunciation of sounds (Eurasian Journal of Humanities and Social Sciences, 2025)
The upbringing of the sound culture of speech includes the ability to clearly pronounce the sounds of the native language, their correct pronunciation, the correct pronunciation of words and phrases, correct speech breathing, as well as the ability to adequately use the power of the voice, the formation of a normal pace of speech and various intonational means of expressiveness (music of speech, logical silence, accents, pace of speech, rhythm and timbre). The sound culture of speech is formed and develops on the basis of a welldeveloped ability to listen to speech.